2018
DOI: 10.3892/or.2018.6490
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of SETDB1 possesses prognostic value and promotes cell proliferation, migration and invasion in nasopharyngeal carcinoma

Abstract: SETDB1, an H3K9‑specific histone methyltransferase, has been described as a repressed transcription marker which triggers tumorigenesis of many types of human cancer. However, there are few studies elucidating the relationship between SETDB1 and nasopharyngeal carcinoma. In the present study, we confirmed that SETDB1 exhibited higher expression levels in nasopharyngeal carcinoma (NPC) tissues and cell lines, compared to these levels in non‑tumor tissues and a normal human nasopharyngeal epithelial cell line. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The knockdown of SETDB1 increased the apoptosis rate in various cancer types (Richter et al, 2009;Spyropoulou et al, 2014;Wong et al, 2016;Huang et al, 2018). Moreover, Shinoda et al demonstrated the relationship between SETDB1 and caspase-3 (Shinoda et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The knockdown of SETDB1 increased the apoptosis rate in various cancer types (Richter et al, 2009;Spyropoulou et al, 2014;Wong et al, 2016;Huang et al, 2018). Moreover, Shinoda et al demonstrated the relationship between SETDB1 and caspase-3 (Shinoda et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…lines was higher in each metastatic line compared to its primary cell line. Studies have reported that the expression of SETDB1 significantly increases the risk of melanoma (Ceol et al, 2011), lung cancer (Lindgren et al, 2012), urothelial carcinoma (Wong et al, 2012), glioma (Spyropoulou et al, 2014), ovarian cancer (Hua et al, 2014), prostate cancer (Sun et al, 2014), breast cancer (Liu et al, 2015), hepatocellular carcinoma (Wong et al, 2016), colorectal cancer (Chen et al, 2017), and solid tumors (Huang et al, 2018). With the increased activity of SETDB1, the excess trimethylation of various tumor suppressors may block gene expression, inducing cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the 5-year overall survival rate of NPC exceeding 80%, the efficacy of NPC treatments plateaued during the previous decade. 22 Genetic factors play an important role in NPC progression and provide a basis for developing novel therapeutic strategies. Here, we investigated the tumor-suppressive role of CYLD in NPC and revealed an underlying CYLD-specific mechanism according to analyses of results from NPC cell lines and clinical specimens.…”
Section: Discussionmentioning
confidence: 99%